1993
DOI: 10.1136/bmj.306.6890.1449
|View full text |Cite
|
Sign up to set email alerts
|

Community mothers' programme: randomised controlled trial of non-professional intervention in parenting.

Abstract: Objective-To see whether non-professional volunteer community mothers could deliver a child development programme to disadvantaged first time mothers for children aged up to 1 year.Design-Randomised controlled trial. Setting-A regional health authority in Dublin. Subjects-262 first time mothers who were delivered during six months in 1989 and who lived in a deprived area of Dublin; 30 experienced mothers from the same community recruited as community mothers.Interventions-All the first time mothers received st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
182
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(189 citation statements)
references
References 3 publications
3
182
0
Order By: Relevance
“…207 Given the success of this first trial, this article described the effort to apply the model to Traveller mothers. Outreach workers were experienced settled community mothers who were given additional training to heighten their awareness of and sensitivity to the needs of the Traveller parents.…”
Section: Fitzpatrick 1997 64mentioning
confidence: 99%
“…207 Given the success of this first trial, this article described the effort to apply the model to Traveller mothers. Outreach workers were experienced settled community mothers who were given additional training to heighten their awareness of and sensitivity to the needs of the Traveller parents.…”
Section: Fitzpatrick 1997 64mentioning
confidence: 99%
“…• Improve parents' verbal responsiveness to children, provide more stimulating activities to children, increase parents' level of reading to children, strengthen children's language and literacy skills, increase children's problem-solving skills, improve school readiness, cognitive skills and academic achievement, and narrow achievement gaps between majority and minority group children (Black et al 1994;Brooks-Gunn and Markman 2005;Johnson, Howell, and Molloy 1993;Landry et al 2012;Myers and Hertenberg 1987;Reese, Sparks, and Leyva 2010;Turner, Nye, andSchwartz 2004/2005;Gardner et al 2003). …”
Section: Evidence That Parenting Programs Work When Implemented Wellmentioning
confidence: 99%
“…• Increase immunization rates, child nutrition levels, and child height and weight (Cooper et al 2002;Johnson, Howell, and Molloy 1993;Super, Herrera, and Mora 1990). …”
Section: Evidence That Parenting Programs Work When Implemented Wellmentioning
confidence: 99%
“…Some authors reported results from the same study at different follow-up time points in separate papers and several authors reported results from the same study in more than one paper. Sixteen [70][71][72]74,[76][77][78]80,[82][83][84][85]87,89,90 (73%) included studies were RCTs, two 73,81 (9%) were non-RCTs, one 86 (5%) was a partially randomised study with two randomised intervention arms and one non-randomised control arm, two 75,88 (9%) were CBA studies and one 79 (5%) was a quasi-RCT. Four studies 73,75,81,88 used clustered allocation.…”
Section: Description Of Studiesmentioning
confidence: 99%